STRATEGI MANAJEMEN PERUBAHAN ORGANISASI DALAM DIGITALISASI LAYANAN TERPADU SEKOLAH DASAR MELALUI APLIKASI SCHOOLTALK - Allinda Hamidah; Titiek Rohanah Hidayati; Erma Fatmawati (EBTIDA': Jurnal Pendidikan Dasar Islam, 2026)
The advancement of information technology necessitates school digitalization as a strategic imperative. This study aims to identify and analyze organizational change management strategies in the implementation of the SchoolTalk application as an integrated service solution at SDI Ar Roudloh Lamongan. Employing a qualitative case study design, data were collected through interviews, observations, and documentation from the principal, teachers, administrative staff, and parents. Thematic analysis was used for data analysis. Findings indicate that the school successfully managed the unfreezing stage (building awareness of digitalization urgency through identification of operational challenges and initial resistance handling) and the changing stage (implementing innovative strategies such as manual cut-off policies, master data, training workshops, WhatsApp notification integration, guided payment corners, and incentive systems to address teacher and parent resistance). Although significant benefits such as administrative efficiency, communication synergy, and home-based learning empowerment have been realized, the refreezing stage (stabilizing change into new operational norms) has not been fully achieved. Long-term success hinges on addressing technical infrastructure barriers, such as internet instability and the lack of backup devices, which threaten the stability of integrated services and the positive impact of digitalization. This study underscores the importance of integrating proactive change management with strengthening the technological infrastructure foundation to realize effective and sustainable integrated services in primary schools. Keywords: Integrated Services, Organizational Change Management, Primary School, School Digitalization, SchoolTalk Application.